2014
DOI: 10.3233/jbr-140068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre-harvest and post-harvest factors on the nutritional quality of strawberry fruits: A review

Abstract: Abstract. In the last years, the nutritional quality of fruits has been widely evaluated and requested by consumers, mainly because of the health effects they provide. As known, these benefits can be due to micronutrients, as vitamins and minerals, but also to phenolic compounds, as flavonoids and ellagitannins. In this context, strawberries represent a very good choice for a diet low in saturated fats and sodium and, at the same time they are rich in fiber, potassium and other minerals, vitamins, and antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 65 publications
1
23
0
2
Order By: Relevance
“…In contrast, the TPC as dry weight and fresh weight both showed a significant decrease before veraison, but this decrease is not always statistically significant when the berry color fully changed. These results are in keeping with the study of Alvarez‐Suarez et al (), who reported that green strawberry fruits of different varieties had the highest level of phenolics and flavonoids than pink or red fruits and that these contents decreased during maturity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the TPC as dry weight and fresh weight both showed a significant decrease before veraison, but this decrease is not always statistically significant when the berry color fully changed. These results are in keeping with the study of Alvarez‐Suarez et al (), who reported that green strawberry fruits of different varieties had the highest level of phenolics and flavonoids than pink or red fruits and that these contents decreased during maturity.…”
Section: Resultssupporting
confidence: 92%
“…This was consistent with a previous study on the contents of five muscadine berry skins taken from grapes cultivated in South China (Nanning‐Guangxi and Pu’er‐Yunnan) (Wei et al, ). Yet a study carried out by Alvarez‐Suarez et al () showed that the flavonols identified in strawberries are QD and KD, being quercetin‐3‐glucuronide the most abundant. With berry development, QD content in “Carlos” and ID in “Noble” changed significantly between 2013 and 2014, but other flavonols, such as MD, QD, and ID in each cultivar did not vary obviously (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Blueberries contain a wide variety of phytochemicals, such as polyphenols and flavonoids, which have been suggested to provide important health benefits due to their antioxidant properties . These compounds are not completely stable and, after harvest, they undergo changes during processing and storage, which may alter their biological activity …”
Section: Resultsmentioning
confidence: 92%
“…30 These compounds are not completely stable and, after harvest, they undergo changes during processing and storage, which may alter their biological activity. 37 Figure 4 displays the changes in TPC and AC of CH-and AL-coated blueberries. A significant correlation effect was observed between TPC and AC of treated blueberries with a Pearson coefficient of 0.78 for CH-coated fruits and 0.70 for AL-coated fruits.…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 99%
“…Statistical data suggests that regular consumption of fruits and vegetables, including berries, is associated with reduced risk of chronic diseases, such as cancer and cardiovascular disease (Chu et al, 2002;Duthie, 2007;Giampieri et al, 2012). These compounds are not completely stable, and, after harvest, undergo changes during processing and storage, which may alter their biological activity (Alvarez-Suarez et al, 2014). Factors that may affect antioxidant activity include maturity, genetic differences, pre-harvest conditions, post-harvest storage and processing.…”
Section: Introductionmentioning
confidence: 99%